Drug Safety of Benzodiazepines in Asian Patients With Chronic Obstructive Pulmonary Disease - Liao, Yi-Hsiang; Chen, Liang-Yu; Liao, Kuang-Ming; Chen, Chung-Yu (Frontiers in Pharmacology, 2020)
Purpose: Many comorbidities, including depression, anxiety, and insomnia, occur in patients with chronic obstructive pulmonary disease (COPD). These patients may be prescribed benzodiazepines (BZDs). However, there are some concerns that benzodiazepines increase the risk of drug overdose, hypercapnic respiratory failure, acute exacerbation and increased mortality. The aim of our study was to evaluate the drug safety of BZDs in patients with COPD. Methods: We used the National Health Insurance Research Database in Taiwan from 2002 to 2016 to perform a retrospective cohort study. We enrolled patients who were exposed to the first prescription of BZDs, non-BZDs or a combination (mix user) after COPD diagnosis. We performed 1:1:1 propensity score matching in three groups. The outcomes were COPD with acute exacerbation and all-cause mortality. Poisson regression analysis was performed to evaluate the incidence rate ratios for the outcomes in the groups. Results: After propensity score matching, there were 2856 patients in each group. After adjusting for confounding factors, we found that compared to BZD users, non-BZD and mix users had nonsignificant differences in outpatient management of acute exacerbations, hospitalization management of acute exacerbations, emergency department management of acute exacerbations and all-cause mortality. BZD and mix groups showed significantly increased admission for acute exacerbation of COPD compared with that of the nonuser group, with IRRs of 2.52 (95% CI, 1.52–4.18; p = 0.0004) and 2.63 (95% CI, 1.57–4.40; p= 0.0002), respectively. Conclusion: BZD, non-BZD, and mix users showed increased COPD-related respiratory events compared to nonusers in Asian subjects.